A situational analysis of training for behaviour change counselling for primary care providers, South Africa - Zelra Malan; Bob Mash; Katherine Everett-Murphy (AOSIS, 2015)
Background: Non-communicable diseases and associated risk factors (smoking, alcohol abuse, physical inactivity and unhealthy diet) are a major contributor to primary care morbidity and the burden of disease. The need for healthcare-provider training in evidence-based lifestyle interventions has been acknowledged by the National Department of Health. However, local studies suggest that counselling on lifestyle modification from healthcare providers is inadequate and this may, in part, be attributable to a lack of training. Aim: This study aimed to assess the current training courses for primary healthcare providers in the Western Cape. Setting: Stellenbosch University and University of Cape Town. Methods: Qualitative interviews were conducted with six key informants (trainers of primary care nurses and registrars in family medicine) and two focus groups (nine nurses and eight doctors) from both Stellenbosch University and the University of Cape Town. Results: Trainers lack confidence in the effectiveness of behaviour change counselling and in current approaches to training. Current training is limited by time constraints and is not integrated throughout the curriculum - there is a focus on theory rather than modelling and practice, as well as a lack of both formative and summative assessment. Implementation of training is limited by a lack of patient education materials, poor continuity of care and record keeping, conflicting lifestyle messages and an unsupportive organisational culture. Conclusion: Revising the approach to current training is necessary in order to improve primary care providers' behaviour change counselling skills. Primary care facilities need to create a more conducive environment that is supportive of behaviour change counselling.